Research advances in understanding the role of interleukin-22 in renal disease - Zhao Dan; Zhu Xiao-yu; Jiang Li-li; Wei Xue-jiao; Long Meng-tuan; Jin Die; Miao Chang-xiu; Du Yu-jun (Linchuang shenzangbing zazhi)
Interleukin 22（IL-22），a member of IL-10 cytokine superfamily，is dominantly produced by innate lymphoid cells and CD4+ T helper subtypes such as Th17 and Th22 cells.And interleukin-22 receptor （IL-22R） is a dimer composed of IL-22R1 and IL-10R2 subunit.IL-22 plays a role by conjugating with IL-22R.Recently IL-22 has gained a lot of interest for its unique functions in maintaining and regaining epithelial integrity.However，IL-22 may play a protective or pathogenic role in the occurrence and development of inflammatory and autoimmune diseases.This review summarized the latest researches of IL-22 in renal injury-related diseases.